Religiosity and Prostitution: A Case Study of Argorejo Prostitution in West Semarang - Setiawan, Ary (Teosofia: Indonesian Journal of Islamic Mysticism, 2017)
One of the various illegal jobs in Indonesia is being a prostitute. It is commonly addressed to a woman, who engages in sexual intercourse for money as the source of livelihood. One of the local prostitution in this country is Argorejo Prostitution at Srikuncorostreet, Argorejo village Kalibanteng, West Semarang, Central Java. What remains unique is that the main activity of prostitutes is not only to serve and to satisfy costumers but also to do some religious activities, such as praying, reciting al-Quran, Fasting and others. The questions of this research are: What is the patterns of religiosity of Muslim prostitutes in Argorejo prostitution and Are there Impact of religiosity understanding pattern to their attitudes and deeds of prostitutes. This research produces the data in the form of notes or verbal words from the people or behaviors that can be observed, with the aim to describe the target's condition of the research according to the real source. Using the Phenomenology approach with a source of research data in use is the primary data source in the form of information from the field by direct observation at Argorejo Prostitution about activities implemented, then secondary data sources such as books, documentation data Argorejo Prostitution and activity report data Argorejo Prostitution. For data collection techniques that are used, among others: observation method, interview, and documentation. Data analysis using is descriptive analysis to clarify suitable with the problems are studied and that data is compiled and analyzed. The result of this research is descriptive about responses of prostitutes toward Islam religion, including the worship that they do and the perspective of religiosity understanding. Prospect in the next is all prostitutes be able to more aware with their religion although their job who have implemented in the past was a mistake that could be forgiven